Creatine kinase and neuromuscular fatigue responses following differing spells of simulated cricket fast bowling. - James W Bray; Chris Towlson; Stephen C Hayes; Mark Fogarty (PLoS ONE)
The fast-bowling action demands repetitive high-intensity whole body movements, imposing complex physical and perceptual demands on players that vary significantly throughout the season. This study aimed to assess and establish practical methods and metrics for quantifying fatigue after four simulated fast bowling spells. Eleven senior club male fast bowlers (age 27.3 ± 7.0 y; body mass 83.7 ± 11.6 kg; height 1.80 ± 0.06 m) completed four different bouts of the modified Cricket Australia-Australian Institute of Sport bowling skills test over consecutive weeks. Neuromuscular function (countermovement jump [CMJ]) and creatine kinase (CK) levels were assessed at baseline, immediately post- (+0 h), and +24 h post-simulation. Perceptual measures (session rating of perceived exertion [sRPE]) and well-being were recorded pre and post fast-bowling simulations, with physical demands (PlayerLoad™) recorded throughout each simulation. Significant reductions in CMJ height were observed at +0 hours (t = 9.789, P < 0.01, d = 0.50) and +24 hours post-simulation (t = 4.051, P < 0.01, d = 0.21) compared to baseline. Moderate correlations were found between deliveries bowled (r = 0.48, P < 0.01), simulation duration (r = 0.49, P < 0.01), PlayerLoad™ (r = 0.41, P < 0.01), sRPE (r = 0.48, P < 0.01), and the change in CK concentration at +24 hours post-simulation. These findings suggest that lower-body neuromuscular function may be compromised following spells of fast bowing for up to 24 hours. Moreover, a 'dose-response' relationship was observed between the change in CK concentrations and PlayerLoad™, sRPE and number of deliveries bowled at +24 hours post-bowling spell. Coaches and support staff could use a combination of tools to monitor training and playing to enhance their ability to make informed decisions about a player's readiness to perform.